AUTOMATIC FISH FEEDER TERJADWAL BERBASIS INTERNET OF THIGS (IoT) DI KOLAM BUNDAR DESA SEMAMPIR KEC. SEDATI KAB. SIDOARJO - Ervin Nurul Affrida; Eva Yuli; Firdha Rosavina; Dina Martha; Putri Amelia; Farhandi Farhandi; Zulfian Misbachul; Dimas Tio; Maria Patricia (Kanigara, 2023)
The existence of technological advances can be used to ease human work in activities or daily work. One example that can be seen is the existence of Internet of Things or IoT technology in the era of the industrial revolution 4.0. Therefore, innovation emerged to create an IoT-based scheduled Automatic Fish Feeder system. The process of making automatic fish feeders uses the ESP8266 microcontroller which is directly integrated with Wi-Fi so that it can be operated remotely. Through this automatic fish feeder, the people of Semampir Village, Kec. Sedati Kab. Sidoarjo is expected to be easier to maintain and cultivate fish. This is because fish feeding can be scheduled and managed remotely and works automatically according to schedule. To provide fish feed, there is no need to come directly to the pond, but you can operate an automatic fish feeder remotely. Villagers also get updated information and broader insights about the existence of tools that can relieve and help provide fish feed automatically.